School commuting behaviors: A time-use exploration - José Ignacio Giménez-Nadal; José Alberto Molina; Jorge Velilla (Global Labor Organization (GLO), 2022)
This paper explores school commuting behaviors of children who attend primary school, high-school, or University, using time use data for a set of countries obtained from the Multinational Time Use Study. We focus on the duration of school commutes, and how they correlate with individual and family characteristics. We also explore the transport modes used, and whether the commuting is done alone. The results show significant differences in school commuting times across countries. Furthermore, we find more time devoted to commuting, and higher rates of commuting done alone, as the schooling level of respondents increases. Means of transport are relatively similar within countries, although they change significantly across countries. This analysis is the first exploration of school, high-school, and University commuting behavior, using time use data that make the results comparable. Our analysis opens doors for future research, and may serve planners in terms of policies promoting specific student mobility.
Keywords: 330; school commuting; transport mode; commuting alone; time use data; MTUS data